2022
DOI: 10.15252/embr.202153801
|View full text |Cite
|
Sign up to set email alerts
|

Piwil2 (Mili) sustains neurogenesis and prevents cellular senescence in the postnatal hippocampus

Abstract: Adult neural progenitor cells (aNPCs) ensure lifelong neurogenesis in the mammalian hippocampus. Proper regulation of aNPC fate has thus important implications for brain plasticity and healthy aging. Piwi proteins and the small noncoding RNAs interacting with them (piRNAs) have been proposed to control memory and anxiety, but the mechanism remains elusive. Here, we show that Piwil2 (Mili) is essential for proper neurogenesis in the postnatal mouse hippocampus. RNA sequencing of aNPCs and their differentiated p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…50 Recently, PIWIL proteins and piRNAs have been demonstrated to be involved in the neurogenesis via regulating proliferation, differentiation, survival, and cellular fate of adult neural progenitor cells in the postnatal hippocampus. 51 Additionally, piRNA's role in regulating neuronal differentiation via interacting with cold shock domain containing RNA binding proteins has been validated in human embryonal carcinoma cells. 52 Furthermore, the same group demonstrated that PIWIL4 modulated neuronal differentiation in NT2 cells.…”
Section: Enriched Motifs Of Pirnas and Their Associated Functionsmentioning
confidence: 99%
“…50 Recently, PIWIL proteins and piRNAs have been demonstrated to be involved in the neurogenesis via regulating proliferation, differentiation, survival, and cellular fate of adult neural progenitor cells in the postnatal hippocampus. 51 Additionally, piRNA's role in regulating neuronal differentiation via interacting with cold shock domain containing RNA binding proteins has been validated in human embryonal carcinoma cells. 52 Furthermore, the same group demonstrated that PIWIL4 modulated neuronal differentiation in NT2 cells.…”
Section: Enriched Motifs Of Pirnas and Their Associated Functionsmentioning
confidence: 99%
“…In addition to Dicer-driven RNAi, data implicate piwi-interacting RNAs (piRNAs), a class of small RNAs, in the control of TEs ( 54 , 55 ). The piRNA pathway is a well-documented anti-TE mechanism acting in the germline, through the generation of piRNAs transcribed from piRNA clusters ( 56 ).…”
Section: Interplay Between the Rnai Pathway And Tesmentioning
confidence: 99%
“…Davide De Pietri Tonelli (Italian Institute of Technology-Genova, Italy) explored the involvement of small noncoding RNAs, such as the Piwi-interacting RNAs (piRNAs), in adult neurogenesis ( Gasperini et al, 2023 ). Depletion of Piwil2 and piRNAs through knockdown or the aging process results in an increased activation of the ROS pathway and inflammation in neural stem cells of the adult mouse hippocampus, ultimately leading to increased astrogenesis.…”
Section: Epitranscriptomic Role In Functional Rnasmentioning
confidence: 99%